2013
DOI: 10.1016/j.aim.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Enumerative meaning of mirror maps for toric Calabi–Yau manifolds

Abstract: We prove that the inverse of a mirror map for a toric Calabi-Yau manifold of the form K Y , where Y is a compact toric Fano manifold, can be expressed in terms of generating functions of genus 0 open Gromov-Witten invariants defined by Fukaya-Oh-Ohta-Ono [FOOO10]. Such a relation between mirror maps and disk counting invariants was first conjectured by Gross and Siebert [GS11a, Conjecture 0.2 and Remark 5.1] as part of their program, and was later formulated in terms of Fukaya-Oh-Ohta-Ono's invariants in the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…This can be rephrased as the conjecture that the SYZ map, defined in terms of orbi-disk invariants, is inverse to the toric mirror map of X (cf. [55, Conjecture 0.2], [16,Conjecture 1.1] and [18,Conjecture 2]). To prove this, knowledge about the orbi-disk invariants is absolutely crucial.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…This can be rephrased as the conjecture that the SYZ map, defined in terms of orbi-disk invariants, is inverse to the toric mirror map of X (cf. [55, Conjecture 0.2], [16,Conjecture 1.1] and [18,Conjecture 2]). To prove this, knowledge about the orbi-disk invariants is absolutely crucial.…”
Section: 2mentioning
confidence: 99%
“…On the other hand, their conjecture is much more general and expected to hold even when X is a compact CY manifold. See [16,Conjecture 1.1] (also [18,Conjecture 2]) for a more precise formulation of the Gross-Siebert conjecture in the case of toric CY manifolds. Corollary 1.7 proves a weaker form of [16, Conjecture 1.1], which concerns periods over integral cycles inX (while here the cycles Γ 1 , .…”
Section: 2mentioning
confidence: 99%
“…If this is the case, then an analogous construction in the case of toric Calabi-Yau manifolds would give an answer to the above question. [6,4], it was proved that the so-called SYZ map, which is defined in terms of generating functions of genus 0 open Gromov-Witten invariants, coincides with the inverse of the toric mirror map for any semi-projective toric Calabi-Yau manifold. The analogue of the SYZ map in the quasimap setting would just be the identity map t(q) = q.…”
Section: 1mentioning
confidence: 99%
“…Enumerative meaning of the mirror map 4 was obtained in the compact semi-Fano toric case and toric Calabi-Yau case [CLT13,CLLT11,CLLT12,CCLT]. It was shown that the mirror map equals to the so-called SYZ map, which arises from SYZ construction and is written in terms of disc invariants.…”
Section: Algorithm To Count Polygonsmentioning
confidence: 99%